Mathematics Learning Devices Development based on Realistic Mathematics Education on Probability - Nana Sepriyanti; Evi Mega Putri (AT-TA'LIM, 2018)
The purpose of thisÂ  research is to develop mathematics learning devices in the form of Lesson Plan (RPP) and Student Assignment (LKPD) based Realistic Mathematics Education(RME) on probability materials in line with curriculum 2013. In addition, this research aims to describe the quality of developed learning devices in both validity and practicality aspects. This is a development research with 4D model including define, design, develop and disseminate. The researcher modified the development model by simplified the model through limit the research up to develop stage by considering the time and the cost. The define stage consists of: a) curriculum analysis; b) student analysis; and c) concept analysis. The design stage consists of: a) Lesson Plan design; b) Student Assignment design; c) instrument design and validation on assessment instrument of learning devices. Meanwhile, the develop stage consists of: a) the validation of learning devices by the expert and mathematics teacher; b) testing; and c) the questionnaire of both teacher and students responses. This research produces mathematics learning devices in the form of Lesson Plan and Student Assignment basedRealistic Mathematics Education (RME) on Probability materials class X. The research findings shows that according to expert and mathematics teacher assessment, the developed learning devices are valid with 3.25 on average for lesson plan and 3.48 on average for student assignment. The result of the teacher response on the questionnaire shows that student response and interview display that mathematics learning devices in the form of lesson plan and student assignment are practical to be used on mathematics learning particularly on probability materials with 3.50 on average for Lesson Plan and 3.30 on average for Student Assignment.